30.1k views
0 votes
2. Solve the inequality for x. Show each step of the solution. 16x > 12(2x – 6) – 24

User Tonito
by
5.7k points

2 Answers

6 votes
Simplifying 2x + 6 = 4x + -2 Reorder the terms: 6 + 2x = 4x + -2 Reorder the terms: 6 + 2x = -2 + 4x Solving 6 + 2x = -2 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 6 + 2x + -4x = -2 + 4x + -4x Combine like terms: 2x + -4x = -2x 6 + -2x = -2 + 4x + -4x Combine like terms: 4x + -4x = 0 6 + -2x = -2 + 0 6 + -2x = -2 Add '-6' to each side of the equation. 6 + -6 + -2x = -2 + -6 Combine like terms: 6 + -6 = 0 0 + -2x = -2 + -6 -2x = -2 + -6 Combine like terms: -2 + -6 = -8 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4 the answer is x=4


User VladP
by
5.0k points
3 votes

Remark

The first thing you should do is to get a program to give you a graph. I use Desmos. We'll talk about the solution shown by the graph when we are done with the solution

Solution

Remove the brackets on the right

16x > 12*2x - 12*6 - 24

16x > 24x - 72 - 24 Combine like terms

16x > 24x - 96 Add 96 to both sides.

16x + 96 > 24x Subtract 16x from both sides.

96 > 24x - 16x

96 > 8x Divide 8

96/8 > x

12 > x

Graph

Now we can discuss the graph. The dotted broken line which separates the white from the pink is x = 12. That's the boundary to this inequality. The line itself is parallel to the y axis. Everything to the left of x = 12 is a possible solution to the inequality if it is a number on the x axis. What to do with the y values is an answer for another day. There are many solutions to this inequality, unlike an equation which has only one at the level of your current math class.

2. Solve the inequality for x. Show each step of the solution. 16x > 12(2x – 6) – 24-example-1
User Pedrouan
by
5.2k points